2017
DOI: 10.1038/tp.2017.205
|View full text |Cite
|
Sign up to set email alerts
|

The BDNF Val66Met polymorphism regulates glucocorticoid-induced corticohippocampal remodeling and behavioral despair

Abstract: The BDNF Val66Met polymorphism has been associated with sensitivity to stress and affective disorders. We therefore sought to model the inter-causality of these relationships under controlled laboratory conditions. We subjected humanized BDNF Val66Met (hBDNFVal66Met) transgenic mice to a history of stress, modeled by chronic late-adolescent corticosterone (CORT) exposure, before evaluating affective-related behavior using the forced-swim test (FST) in adulthood. While hBDNFMet/Met mice had a depression-like ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 72 publications
3
27
1
Order By: Relevance
“…It should be noted that, in terms of the two-hit hypothesis, there are studies which show that a second hit actually led to improvements, and some genetic polymorphisms, including BDNF Val66Met polymorphism, may actually increase resilience. For example, a recent study showed that BDNF Met/Met transgenic mice had spatial and fear-associated memory deficits, but corticosterone treatment recovered this phenotype ( Notaras et al, 2017 ).…”
Section: Interaction Between Bdnf Val66met Polymormentioning
confidence: 99%
“…It should be noted that, in terms of the two-hit hypothesis, there are studies which show that a second hit actually led to improvements, and some genetic polymorphisms, including BDNF Val66Met polymorphism, may actually increase resilience. For example, a recent study showed that BDNF Met/Met transgenic mice had spatial and fear-associated memory deficits, but corticosterone treatment recovered this phenotype ( Notaras et al, 2017 ).…”
Section: Interaction Between Bdnf Val66met Polymormentioning
confidence: 99%
“…This finding suggests that chronic stress potentiates the fear circuitry into adulthood in the Met carriers, thereby increasing their susceptibility to fear-and anxiety-related psychiatric disorders such as PTSD 8,14 . With this transgenic mouse model, the same research group showed that the Val66Met polymorphism acts as a regulator of glucocorticoid-induced changes in stress sensitive molecules across corticohippocampal regions 15 . In line with this, a study investigated extinction of conditioned fear responses in genetic knock-in mice as well as humans in order to understand the effect of this polymorphism, demonstrating that the extinction learning was impaired in Met allele carriers relative to non-Met allele carriers for both mice and humans 16 .…”
mentioning
confidence: 99%
“…119 In another study, Val66Met mice that were subjected to the forced-swim test showed the phenotype of behavioural despair at baseline, which only appeared in Val/Val mice after chronic corticosterone administration during late adolescence. 120 Hippocampal memory function of Val66Met mice was also found to be more sensitive to glucocorticoid signalling. 121 Clinical data It has been postulated that Val66Met could convey an increased susceptibility to stress.…”
Section: Associations Between Elsa Bdnf and The Val66met Polymorphismentioning
confidence: 96%